Experimental study on ignition and combustion of coal-rice husk blends pellets in air and oxy-fuel conditions. Issue 4 (August 2020) - Wang, Chengxin; Bi, Haobo; Jiang, Xuedan; Jiang, Chunlong; Lin, Qizhao
Abstract: The ignition and combustion characteristics of anthracite-rice husk (AC-RH) and bituminous coal-rice husk (BC-RH) pellets were investigated in a vertical heating tube furnace under different experimental condition, for gas temperature (873 K–1073 K) and under air and different oxygen concentration (21–70%) in CO2 /O2 atmosphere. The investigation of the ignition and combustion characteristics focused on ignition mechanism, ignition delay, ignition temperature and combustion process. AC-RH pellets had two ignition mechanism in CO2/O2 atmosphere: homogeneous ignition of volatile and heterogeneous ignition of char. Heterogeneous ignition region decreased while homogeneous ignition increased as rice husk blending ratio increased in oxygen concentration-gas temperature plane. Only homogeneous ignition was observed when rice husk blending ratio was 30%. As for BC-RH pellets, only homogeneous ignition occurred in all experimental conditions. The effect of the rice husk blending on the anthracite was more pronounced than the bituminous coal for ignition mechanism. As oxygen concentration increased, a significant reduction in ignition delay and ignition temperature was observed at low rice husk blending ratio and low gas temperature. but at 1073 K, high oxidizer temperature weakened the effect of biomass blending and oxygen concentration on ignition delay and ignition temperature. Meanwhile, at 20% and 30% rice husk blending ratio, it also weakened the effect of oxygen concentration and oxidizer temperature on ignition delay and ignition temperature. In contrast, blending ratio had a more significant effect on ignition behavior. The replacement of N2 by CO2 at the same oxygen concentration contributed to an increase in ignition delay time and internal ignition temperature, which suppressed the ignition behavior. Different ignition mechanisms corresponded to different combustion processes. Highlights: The ignition and combustion behavior of coal-biomass blend pellet was investigated. The critical condition of the transition for ignition mechanism was found. The effect of Tg, O2% and BRH on ignition delay and temperature was discussed. The effect of RH blending on anthracite was pronounced than bituminous coal.